Effect of Foreign Aid on Educational Development in Nigeria - Mukaddas, Tijjani Mohammed (Quest Journal of Management and Social Sciences, 2019)
Background:Education is necessary for the economic growth and political stability of any nation. Due to the lack of resources, Nigeria does not pay necessary attention to education. In recent years Nigeria has reduced the budgetary allocation for education sector. Like in other sectors, Nigeria relies heavily on foreign aids for the development of the educational institutions. Objectives:The study aims at assessing the effect of foreign aid on educational development in Nigeria and to give policy recommendations based upon the conclusion drawn from this study. Methods:The study, conducted in Nigeria, employed descriptive survey research design and data werecollected using key stakeholders questionnaire as research tools. Data were analyzed using descriptive and inferential statistics for research questions and t-test statistics to answer the research hypothesis. Results:Findings from this study revealed that foreign aid has positively affected Nigeria education in terms of infrastructure, SDGs, UBE, science and technology, human resources and ICT. Conclusions:The foreign aid to education has a positive impact on Nigerian educational development. Implications:The result generated from this study can be considered by education policy makers of Nigeria and concerned authorities. Recommendations:The study recommended that donor countries/agencies should allow Nigeria to design and formulate its own policies according to her culture and traditions. It is also recommended that foreign aid intervention should be carried out more in rural communities especially in the area of critical infrastructures in Nigerian schools.